Junta de civilização e conquista dos índios e navegação do Rio Doce: fronteiras, apropriação de espaços e conflitos (1808-1814) - Silva, Tarcísio Glauco da (2006)
This research job has as object the Junta de Civilização e Conquista dos Índios e Navegação do Rio Doce, created in 1808, with the objective to fight the botocudos indians and to initiate the effective conquest and occupation of Minas Gerais captaincy east region. The decay of the mining leads to a search of productive options and, in this context, the new land appropriation for the exploitation in agricultural activities pressures the movement of the borders captaincy occupation, particularity the east region: the average Doce river. The region understood aboriginal areas of vast forest and tribes and the increase of the contact between indians and colonists led to a new outbreak of the attritions between the two groups. To try to decide this problem and to promote `civilization' of the area was created the Junta do Rio Doce. This job looks for focusing the region gradual occupation throughout century XVIII, where restricted areas to the occupation become explored and the attention goal of the captaincy government attention the captaincy government. So, the Junta do Rio Doce can be seen as the main agent of settling, at the beginning of century XIX. Through the distribution of lands the new colonists and the aboriginal groups control through the retiring then, looked themselves to create the ideal conditions for an increase of the white population in the region. The retiring in the region managed for the Junta do Rio Doce, can be seen more as a strategy of removal from the indian of its lands than an initiative to integrate this indian to the Portuguese society. Through the research in Act Books of the Junta de Civilização e Conquista dos Índios e Navegação do Rio Doce, we look for to analyze as it was its performance to reach its objectives, that can thus be summarized: to become the safe area and to guarantee its occupation.